Purulent Hydradenitis. Part II - A. N. Rodionov; A. V. Sobolev; S. V. Skrek; P. Wolkenstein; A. A. Yunovidova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Purulent hydradenitis is a chronic relapsing disease that affects 4% of the population, caused by uncontrolled growth of hair follicle and apocrine gland cells, which leads to the development of autoimmune and then septic inflammation. The provoking factors are obesity, smoking, formation of apocrine glands in the body. The variety of subordinates of Suppurative hydradenitis, differences in the prognosis and course of the disease, as well as the need to manage patients with this pathology in the surgical department, determine the standardization of the therapeutic algorithm and the objectification of the degree of clinical response to the therapy using scoring scales.